2018
DOI: 10.1002/eco.2028
|View full text |Cite
|
Sign up to set email alerts
|

Drip heterogeneity and the impact of decreased flow rates on the vadose zone fauna in Ciur‐Izbuc Cave, NW Romania

Abstract: The aim of this study was to better understand the unsaturated zone of a karst massif habitat for aquatic fauna by defining patterns of cave drip flow rates. Dripping was logged over a period of 4 years at three points inside Ciur-Izbuc Cave (north-western Romania). Drip rates have been analysed at different scales and also compared with rainfall. The results show the individual behaviour of drips on daily, monthly, and yearly timescales and no significant correlations between the three drip points or between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Changes Throughout the world, at least some of these problems are recognized and sometimes carefully dealt with [16][17][18][19][20][21][22][23][24][25]. Monitoring programs have been enforced for both old show caves [6] and newly discovered caves [26].…”
Section: Threat Cause Effectsmentioning
confidence: 99%
“…Changes Throughout the world, at least some of these problems are recognized and sometimes carefully dealt with [16][17][18][19][20][21][22][23][24][25]. Monitoring programs have been enforced for both old show caves [6] and newly discovered caves [26].…”
Section: Threat Cause Effectsmentioning
confidence: 99%
“…For instance, Musgrove and Banner (2004) showed that the hydro-geochemistry ( 87 Sr/ 86 Sr, Sr/Ca, and Mg/Ca) of different drip sites in a cave in central Texas is temporally and spatially variable. Other studies showed that also the drip rate of drip sites within the same cave (Ciur-Izbuc Cave, Romania) can be significantly different and decoupled from rainfall (Moldovan et al, 2018). This is further supported by a study identified a chaotic discharge behavior in Cathedral Cave (Australia), which especially influences growth-rate dependent climate proxies (Mariethoz et al, 2012).…”
Section: Implications For Speleothem-based Palaeoclimate Reconstructionsmentioning
confidence: 76%
“…Water-soluble radon could Atmosphere 2021, 12, 1207 2 of 12 increase indoor radon activity, which is known to cause lung cancer [16] and has also been linked with induced stomach cancer [21]. Additionally, contamination of the public drinking water supply by chemical and biological pollutants occurs often in Romania according to scientific [22][23][24] and public records (National Institute of Public Health). One specific example is represented by the spring waters in karstic regions which originate from groundwater.…”
Section: Introductionmentioning
confidence: 99%